Makna Islam dalam Al-Qur’an: Studi Penafsiran ‘Abdullāh Yūsuf ‘Alī dan Muḥammad Asad - Ulfah Nur Azizah; Rini Haryani (Refleksi: Jurnal Kajian Agama dan Filsafat, 2024)
This research discusses the negative image of Islam that is perceived by some elements of society and religious figures, who often view parties outside of Islam as threats. This creates a dichotomy between the majority and the minority, which has implications for the emergence of violence and oppression. Using qualitative methods with a manhaj al-muqāran approach, this research examines the interpretations of ‘Abdullāh Yūsuf ‘Alī and Muḥammad Asad, both of whom offer inclusive perspectives on Islam. The research results show that although there are differences in approach, both agree that Islam teaches the values of tolerance, religious freedom, and total surrender to God as the path to salvation. This finding confirms that Islam is not an exclusive religion but rather prioritizes coexistence in peace. This research contributes to healing the psychological burden of Muslims and opens insight into the meaning of Islam, which is relevant in the contemporary era.